A soccer-specific balance training program for hamstring muscle and patellar and Achilles tendon injuries. An intervention study in Premier League female soccer - Kraemer, R.; Knobloch, K. (The American Journal of Sports Medicine, 2009)
Background: A soccer-specific balance training has been shown to decrease injury incidence of the anterior cruciate ligament and ankle sprains in randomized controlled trials. However, hamstring injuries and tendinopathy remain significant issues in soccer.